PENGUKURAN PRODUKTIVITAS LANTAI PRODUKSI MENGGUNAKAN METODE OBJECTIVE MATRIX (OMAX) DAN FAULT TREE ANALISIS (FTA) - Fajar Triawan, Dimas Fajar Triawan; Andung Jati Nugroho (Lembaga Pengembangan Kinerja Dosen, 2023)
PT Madubaru Madukismo is a company engaged in the manufacture of granulated sugar. The problem faced by PT Madubaru Madukismo is that the company has not reached the set production target. It is known that the production target set by the company is 30,000 quintals per month. So for measuring productivity using the objective matrix (OMAX) and fault tree analysis (FTA) methods where the objective matrix (OMAX) is a partial productivity measurement system developed to monitor productivity in each part of the company with productivity criteria in accordance with the existence of that part, and fault tree analysis (FTA) is a method used to analyze the risk that causes a failure. There are five measurement ratio criteria, namely production efficiency productivity, raw material efficiency productivity, production target effectiveness productivity, machine work effectiveness productivity and number of employees productivity. Then the results obtained The highest productivity value achieved during measurements in the period May to October 2022 was in August with a productivity level of 864 and the lowest was achieved in May of 35, as well as an analysis of indicators from the calculation of the ratio 1 to 5, it can be seen that the lowest ratio is at the 3, namely the effectiveness of production targets and ratio 1, namely productivity, production efficiency. Based on the minimum cut-set, the basic events that can cause a low ratio 3 and 1 are the lack of suppliers from sugar cane farmers, workers' working hours are reduced because raw materials are late, production room temperature is hot, and does not match the jobdesk Keywords: Productivity, Ratio, Criteria, Objective Matrix (OMAX), and Fault Tree Analysis (FTA).